Geoparsing history: Locating commodities in ten million pages of nineteenth-century sources. Issue 3 (2nd July 2016) - Clifford, Jim; Alex, Beatrice; Coates, Colin M.; Klein, Ewan; Watson, Andrew
ABSTRACT: In the Trading Consequences project, historians, computational linguists, and computer scientists collaborated to develop a text mining system that extracts information from a vast amount of digitized published English-language sources from the "long nineteenth century" (1789 to 1914). The project focused on identifying relationships within the texts between commodities, geographical locations, and dates. The authors explain the methodology, uses, and the limitations of applying digital humanities techniques to historical research, and they argue that interdisciplinary approaches are critically important in addressing the technical challenges that arise. Collaborative teamwork of the kind described here has considerable potential to produce further advances in the large-scale analysis of historical documents.